Analysis of Cooperative Learning Models on Islamic Education Learning Outcomes of Junior High School Students - Elfi Putra; Cisia Padila; Pela Safni; Ahmad Sabri; Sasmi Nelwati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Improving the quality of education is a major focus in many countries, including Indonesia. One of the key elements in achieving this goal is through effective learning processes in schools. Among the various learning strategies available, the cooperative learning model has attracted the attention of many educators, especially at the junior high school level. This model emphasizes cooperation among students to achieve a common learning goal. This article aims to analyze the effect of cooperative learning model on learning outcomes of junior high school students. Literature review analysis by analyzing various relevant research sources, such as scientific journals, scientific articles, and research reports. The results of the analysis show that the cooperative learning model has a positive influence on the learning outcomes of junior high school students. This is evidenced by several findings, namely: increased learning scores, increased learning motivation, increased cooperation skills, increased critical and creative thinking skills, increased self-confidence and independence, increased socialization and communication skills. Further analysis needs to be conducted to explore different types of cooperative learning models that are effective for different subjects and for diverse student groups.